Diffusion of Knowledge in a Municipal Enterprise – a Case Study - Pietruszka-Ortyl, Anna; Prorok, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The study begins by presenting the theoretical foundations on which the concept of knowledge diffusion is based and discusses how municipal enterprises function. The central question the paper seeks to answer is how knowledge is diffused in selected municipal enterprises. The following questions were answered: What are the organizational behaviours of the managers and employees of the verified organization in the context of knowledge transfer? How frequently are individual knowledge distribution instruments used in municipal units? The main objectives of the study were: to identify conditions for the diffusion of knowledge, taking into account its subprocesses and the tools used. Second, to construct, based on the case study, a model solution covering individual elements of the knowledge diffusion system in municipal enterprises. On the basis of the theoretical considerations, the initial identification of knowledge diffusion subprocesses occurring in a municipal enterprise was made. The research was carried out at the Municipal Water and Sewage Enterprise SA. Recommendations which were selected are in line with ideas of prosumerism, corporate social responsibility or coopetition, characteristic for the knowledge-based economy. Taking into account the special nature of municipal enterprises, a number of prompts have been selected that will be developed in the future to promote the improvement of knowledge diffusion and may also contribute to the creation of a knowledge diffusion model in such organizations.